Multi-Aspect Temporal Topic Evolution with Neural-Symbolic Fusion and Information Extraction for Yelp Review Analysis: A Comprehensive Deep Learning Framework - Irfan Ali, (Indian Journal of Artificial Intelligence and Neural Networking (IJAINN), 2025)
The exponential growth of user-generated content on review platforms like Yelp presents unprecedented opportunities for understanding consumer behaviour and market dynamics through advanced natural language processing. However, existing approaches face critical limitations: traditional topic models fail to capture fine-grained aspect-specific insights, neural methods lack integrated information extraction capabilities, and temporal dynamics modelling remains underdeveloped. Extracting actionable intelligence from unstructured review text is computationally challenging due to inherent linguistic complexity, temporal variability, multi-dimensional sentiment patterns, and the need to understand geographic market variations. These challenges necessitate a comprehensive framework that simultaneously addresses aspect extraction, topic discovery, temporal evolution, and market analysis. We propose the MultiAspect Temporal Topic Evolution with NeuralSymbolic Fusion and Information Extraction (MATTE-NSF-IE) framework, a novel end-to-end system for analysing restaurant reviews. The framework integrates four synergistic components: (1) a transformer-based information extraction module leveraging RoBERTa, VADER, and BERT for aspect ex- traction, sentiment classification, and named entity recognition; (2) a neural-symbolic topic modeling architecture combining Latent Dirichlet Allocation with TF-IDF weight- ing for aspect-aware topic discovery; (3) a temporal forecasting system using ensemble moving average prediction for sentiment trend analysis; and (4) a geographic market analysis module with statistical validation through Mann-Whitney U tests. We evaluated MATTE-NSFIE on the Yelp Open Dataset, analyzing 3,000 highquality restaurant reviews spanning 2005-2018 from 1,467 businesses across 248 metropolitan areas. The information extraction module achieved 70.0% F1- score for aspect extraction, 70.8% for sentiment classification, and 97.2% for named entity recognition. Topic modelling generated eight coherent aspect-specific topics with an 87.5% diversity score and 0.208 NPMI coherence. Temporal analysis achieved a mean absolute error of 17.9% in sentiment forecasting. Market analysis revealed statistically significant geographic patterns (p < 0.05) across 10 major cities, identifying variations in health trends (3.57-4.38), service priorities (0.72-0.78), and price sensitivity differences (0.44-0.57). The framework enables realtime business: intelligence applications, personalised recommendation systems, and comprehensive market analysis. Our approach provides actionable insights for restaurant management, investment decisions, understanding consumer behaviour, and locationbased market intelligence, positioning it for highimpact deployment in both academic research and industry applications.